Evolution of HIV-1 subtype C immune responses during acute and chronic HIV infection - Gamieldien, Hoyam (Division of Virology, 2014)
The aim of this study was to compare the magnitude and breadth of HIV-specific T cell responses to HIV Gag and Nef mounted during acute HIV infection with those that emerged during chronic infection and to investigate the association of these responses with subsequent HIV disease progression (CD4 counts and plasma viral loads).